(untitled) (Research, Society and Development, 2023)
Objective: consists of carrying out a systematic review of the literature, focusing on studies that address the effectiveness of microencapsulation of Lacticaseibacillus in dairy foods. Methodology: the search was conducted in renowned databases, such as Scopus, Pubmed, Scielo and Lilacs, following the PRISMA methodological guidelines, with the inclusion of data from the period between 2018 and 2023. At the end of the search, 15 articles were selected, meeting the established eligibility criteria. Results: revealed a preference for the freeze-drying technique in microencapsulation, providing stability over time. The most frequently studied foods include whey protein, yogurt and cheese. The encapsulation rate, consistently exceeding 90%, provided significant insights into the effectiveness of the techniques used in this process. The review identified the need to update terms, such as "Lacticaseibacillus", highlighting the importance of keeping terminology aligned with scientific advances and updated taxonomy. Conclusion: It is highlighted that a deeper understanding of the interactions of Lacticaseibacillus with the intestinal microbiota can open avenues for personalized therapies, thus contributing to the promotion of gastrointestinal and immunological health. The encapsulation rate, often exceeding 90%, highlights the effectiveness of this approach. It is therefore highlighted that research in this field is essential to optimize the use of these bacteria as probiotics, promoting significant benefits for human health.